Exploiting Hydel Power Potential to Maintain Energy and Water Securities in Kerala - K. Shadananan Nair (International Conference on Small Hydropower - Hydro Sri Lanka, 22-24 October 2007, 2007)
Demands in energy have been increasing tremendously in the state of Kerala in India, associated with rise in population, changing climate, rapid urbanization, industrialisation and the changing life styles. This heavy rainfall region that depends on cheap hydroelectric power for most of its energy needs has not yet fully utilised the water potential. Shortage of power leads to conflicts over allocation and timing of supply. There are limitation for large projects due to geological and geographical factors and also uncertainties in climate. There are options for maximum utilisation of available sources including conversion of existing dams multipurpose, modernisation of machinery, and construction of more mini hydel power plants. This will also solve issues related to water shortage that is the result of inadequate conservation and management practices. The State lacks an appropriate policy for energy and water. This paper analyses the various issues associated with power and water crisis and explores the possibilities of sustainable exploitation of hydel power in Kerala.